Creating a gateway that enables large‐scale science coopetition. (10th April 2014) - Crivelli, Silvia; Dooley, Rion; Holmes, Raquell; Mock, Stephen; The WeFold Community; Wilkins‐Diehr, Nancy; Gesing, Sandra; Kiss, Tamas
Summary This paper describes the WeFold gateway that provides a social and technical environment for the first large‐scale attempt at collaboration within the context of the Critical Assessment of techniques for protein Structure Prediction (CASP) competition. CASP is a biennial worldwide experiment created 20 years ago to advance the field of protein folding, one of the grand challenges in modern science. The WeFold experiment was started in CASP10 (the 10th CASP) to bring together scientists from different disciplines to brainstorm online, share ideas and codes, and synergistically develop new methodologies. The goal is to positively shake up the field to stimulate breakthrough advances. Copyright © 2014 John Wiley & Sons, Ltd.